PP26 Shift From Regional To Federal Funding: Methodological Considerations. (2019) - Newton, Skye; Kessels, Sharon; Vogan, Arlene; Merlin, Tracy
Abstract : Introduction: Australia has a two-tier public funding system, and many genetic tests are funded by different states and territories prior to being considered for public funding by the Federal government. In this context, health technology assessments (HTAs) of genetic tests for heritable conditions are problematic. We aimed to discuss the possible impacts on HTA methodology of a shift from regional to federal funding for genetic testing for heritable conditions. Methods: Several HTA reports and economic models on genetic tests considered by the Medical Services Advisory Committee (MSAC) were reviewed and compared to 'real world' clinical practice. Results: Every HTA of germline testing performed for the MSAC have so far compared genetic testing versus no genetic testing. However, testing for BRCA1/2 for patients with breast cancer currently occurs in Familial Cancer Centres, and testing for germline mutations for familial hypercholesterolaemia currently occurs through specialist lipid clinics. In both settings, the index patient and family members are given multidisciplinary support, including genetic counselling. The HTA comparison therefore did not reflect what the true clinical and cost-effectiveness impact of federal funding would be. Federal funding means that tests may be ordered by a broader range of specialists or general practitioners. The evidence identified was predominantly sourced from specialised centres, where knowledge regarding how to interpret the tests is high. The clinical utility of these tests largely depended on how clinicians understood and conveyed the results. Conclusions: The benefit of testing may have been overestimated due to the comparator and setting used (i.e. specialised and centralized care, associated with high clinical utility). Any HTA of genetic testing for heritable conditions, which could result in a shift in the delivery of testing or care for the patient, should consider the applicability of the evidence identified. Further, it should assess the subsequent impact this may have on the effectiveness and cost-effectiveness of the test and the quality of care provided for patients and their family.